Research on the Development of Architectural Conditions for Civil Repairs in Afghanistan - Akbari, Saied Hamayon Shah (Journal for Research in Applied Sciences and Biotechnology, 2024)
During the formation of fidalism, the culture of urbanization, which was considered the necessary link in the slave society, decreased, but the Centers of Buddhist culture in Afghanistan continued to operate even after the Arab conquests in the 7th century AD. At the beginning of the 5th century, from the depths of Central Asia, the Gochhanda Yaftali tribes invaded the territory of Afghanistan, which eventually led to the extinction of the Kushan Empire. Coexistence and interaction with neighbors in a peaceful and sometimes non-peaceful way of agricultural units with nomadic tribes is one of the main features of the historical development of the people of Afghanistan and Asia. By settling in the lands of Afghanistan and accepting the local culture and enriching it with their tribal traditions, the nomadic tribes helped a lot in the emergence of the process of a new social and cultural nature in the country. The conquests of the Arab caliphs, which began in the seventh century, and as a result of the interaction of their culture with the cultural traditions of the local people, led to the creation of a new culture. And Islamic religion replaced Buddhism and other religious beliefs. Buildings for worship were built called mosques, Eidgah’s, schools and caravanserais. The formation of large commercial and handicraft cities, which took place in the development of literary and architectural sciences, which took place in the middle of the centuries of the feudal period. The Ghaznavid dynasties (10th-12th centuries) and the Ghurids, the "king of the mountains" in the 12th century, had a significant impact on the history of the early Middle Ages. In the engineering of the cities of the Ghaznavid period, the buildings of the city (Ghazni, Qala-e-Bast, Lashkargah) and also in the engineering of most of the buildings of the Ghurid dynasty (a minaret in the mountainous region of Jam), the ideological characteristics of that era have been expressed in the language of engineering. In the modern era, after the wars and the destruction of cities and places in the country, the migrations that took place as a result of the civil wars and the return to the country, brought different cultures to the country. Also, by mixing new cultures with local traditions, it caused cities and places to take a new shape. Thus, it influenced the development of Afghan architecture and the growth of modern architecture. This will be of particular importance with the combination of local architectural culture and traditions in Afghanistan.